Investigating the relationship between executive functions and patterning knowledge in children aged 4 to 7 years - Şanlı Karmaz, Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This study aimed to investigate to what extent executive functions (cognitive flexibility, working memory, and inhibitory control) predict patterning knowledge in children aged 4 to 7 years, with and without considering their ages. The sample comprised 50 children and their parents who volunteered from different provinces of Turkey. The participants, involving 30 girls and 20 boys, ranged in age from 47 to 83 months, with an average age of 66.36 months. Four measures were used in the study, including an online Early Patterning Assessment scale, the Dimensional Change Card Sort (DCCS) test, the Childhood Executive Functioning Inventory (CHEXI) parent form, and a post-study survey. A hierarchical multiple regression analysis was conducted with age, cognitive flexibility, and working memory variables, which were significantly associated with patterning knowledge. The age of children was the variable that most strongly predicted patterning knowledge. In addition, cognitive flexibility had a higher role in patterning when considered with age, whereas it had a much less role regardless of age. However, working memory did not predict patterning knowledge. This study provided valuable insights by investigating the role of executive functions in patterning knowledge and suggesting that a significant proportion of the contribution of executive functions to patterning knowledge is age dependent.
Keywords: Short-term memory.; Cognitive dissonance.